Fruit of the dead : a novel - Lyon, Rachel, 1983- (Scribner, 2024)
An electric contemporary reimagining of the myth of Persephone and Demeter set over the course of one summer on a lush private island, about addiction and sex, family and independence, and who holds the power in a modern underworld. Camp counselor Cory Ansel, eighteen and aimless, afraid to face her high-strung single mother in New York, is no longer sure where home is when the father of one of her campers offers an alternative. The CEO of a Fortune 500 pharmaceutical company, Rolo Picazo is middle-aged, divorced, magnetic. He is also intoxicated by Cory. When Rolo proffers a childcare job (and an NDA), Cory quiets an internal warning and allows herself to be ferried to his private island. Plied with luxury and opiates manufactured by his company, she continues to tell herself she's in charge. Her mother, Emer, head of a teetering agricultural NGO, senses otherwise. With her daughter seemingly vanished, Emer crosses land and sea to heed a cry for help she alone is convinced she hears. Alternating between the two women's perspectives, Rachel Lyon's Fruit of the Dead incorporates its mythic inspiration with a light touch and devastating precision. The result is a tale that explores love, control, obliteration, and America's own late capitalist mythos. Lyon's reinvention of Persephone and Demeter's story makes for a haunting and ecstatic novel that vibrates with lush abandon. Readers will not soon forget it.